Reading culture and library use of students in selected government secondary schools in Ogbomoso, Oyo state, Nigeria (2010)
"The main objective of this study was to identify the reading habits and library use of selected secondary school students in Ogbomoso, Oyo state, Nigeria. Two stage random selection technique was used in selecting the secondary schools and the students used for the study. Fifteen schools and three hundred (300) students who are in the senior secondary schools (SSS) classes were used. Out of this, two hundred and ninety-one (97%) students returned usable questionnaires. The study was set to test five null hypotheses and seven research questions. The results of the hypotheses showed that only the class of the students had effect on their library use possibly because they were preparing for entrance examination into higher institutions. The school, parents' occupation, gender and age does not have any effect on the library use of the students. The study revealed that 122 (4 1%) respondents spent less than 1 hour in the library. The results of the study also showed that 57% students utilized textbooks whenever they visited the library (N=2.19) while newspapers/magazines (N= 1.36), non fiction books (N= 1 -45) and fiction books (N=1.60), were not utilized during library visits by the respondents. It was also observed that in most of the secondary schools visited, books available in their libraries were old and in bad condition, and not inviting enough to stimulate additional reading. In addition, the respondents have low opinion on their reading habits and this could account for their Iow leveI of reading. "